Retinal vascular density as a potential biomarker of diabetic cerebral small vessel disease - Huang, Yinqiong; Wang, Siyun; Cai, Chi; Huang, Xinwei; Chen, Yan; Wu, Xiaohong; Zhang, Yiping; Zhang, Yan; Lin, Xiahong (Diabetes, obesity & metabolism, 2024)
Aim The retina and brain share similar anatomical and physiological features. Thus, retinal imaging by optical coherence tomography angiography (OCTA) might be a potential tool for the early diagnosis of diabetic cerebral small vessel disease (CSVD). In this study, we aimed to evaluate retinal vascular density (VD) in diabetic CSVD by OCTA imaging and explore the associations between retinal VD and cerebral magnetic resonance imaging (MRI) markers and cognitive function. Methods In total, 131 patients were enrolled, including CSVD (n = 43) and non‐CSVD groups (n = 88). The VD and foveal avascular zone of the retinal capillary plexus were measured with OCTA. A brain MRI was performed. Results MRI imaging showed that in the diabetic CSVD group, white matter hyperintensities (WMHs), particularly deep WMHs (58.82%), are the most common MRI marker, followed by cerebral microbleeds in the subtentorial and cortical areas (34.78%). The CSVD group showed increases in the prevalence of cognitive dysfunction (p = .034) and depression (p = .033) and decreases in visuospatial/executive ability and delayed recall ability. In the CSVD group, VDs of the macular superficial vascular plexus (32.93 ± 7.15% vs. 36.97 ± 6.59%, p = .002), intermediate capillary plexus (20.87 ± 4.30% vs. 23.08 ± 4.30%, p = .005) and deep capillary plexus (23.54 ± 5.00% vs. 26.05 ± 4.20%, p = .003) were lower than those of the non‐CSVD group. Multiple linear regression analysis showed that VD of the macular superficial vascular plexus was independently associated with cerebral microbleeds. Meanwhile, VD of the macular intermediate capillary plexus was associated with white matter lacunar infarcts after adjustment. Conclusions Diabetic CSVDs are characterized by MRI markers, including deep WMHs and cerebral microbleeds, and showed impaired cognition with decreased visuospatial/executive ability and delayed recall ability. OCTA imaging revealed a significant decrease in retinal microvascular perfusion in diabetic CSVD, which was related to MRI markers and cognitive function. OCTA might be a valuable potential measurement for the early diagnosis of CSVD.